PENGARUH BRAND AWARENESS DAN PERCEIVED QUALITY TERHADAP REPURCHASE INTENTION MELALUI CUSTOMER SATISFACTION PADA PRODUK DBD POWDER MEDAN - Juan Sakti Gultom; T. Lyza Tahura Chairunnisa; Muller Tamba (VALUE, 2021)
This study was conducted to determine the effect of brand awareness and perceived quality on repurchase intention mediated by customer satisfaction separately or together. The population is taken from customers who come and buy the company's products with an average of 3,250 consumers per month, a sample of 97 respondents drawn based on the slovin formula. Questionnaires are used to collect data with the data source is primary data. Data analysis techniques consist of data quality test, classical assumption test, path analysis and hypothesis testing. This study gives results that partially brand awareness has a positive but not significant effect on customer satisfaction, perceived quality has a positive and significant effect on customer satisfaction. Brand awareness and perceived quality partially have a significant effect on repurchase intention, and customer satisfaction has a positive and significant influence on repurchase intention at DBD Powder Medan. Simultaneously shows that brand awareness and perceived quality simultaneously have a significant effect on customer satisfaction. Brand awareness, perceived quality and customer satisfaction together have a positive and significant effect on repurchase intention in DBD Powder Medan.